Double-counting of investment - Robert J. Barro (Center for Economic Studies and ifo Institute (CESifo), 2019)
The national income and product accounts double-count investment, which enters once when it occurs and again in present value when the cumulated capital leads to more rental income. From the perspective of resources available intertemporally for consumption, the double-counting issue implies over-statement of levels of GDP and national income. There is also exaggeration of capital-income shares. A proposed alternative measure of product and income involves a form of full expensing for gross investment. In the steady state, revised product and income correspond to consumption. Outside of the steady state, the measure deviates from consumption because full expensing relates to the long-run flow of gross investment, not the current flow. At a practical level, the new concept requires only an extension from the standard depreciation rate to an effective rate that adds in the economy's expected long-run rate of economic growth.
Keywords: 330